Outcome of Titanium Elastic Nailing in Fracture Shaft of Femur in Children Aged 6-16 Years - A Short Term Study - Jha, Ranjib Kumar; Gupta, Yogendra; Karn, Navin; Ghimire, Nischal (Nepal Orthopaedic Association Journal, 2016)
BACKGROUND: Fracture shaft of femur is one of the most common major pediatric injuries. Management of femoral diaphyseal fractures is controversial in the age group of 6-16 years. We aim to study the short term outcome and complications of such fractures treated operatively with titanium elastic nail system (TENS). MATERIALS AND METHODS: Thirty six children aged 6 to 16 years with femoral diaphyseal fractures, who were treated with retrograde TENS from July 2011 to December 2014 were included in the study. Closed fractures were classified according to Winquist-Hansen as grade I(n-25), grade II(n-7) and grade III(n-4) and open fractures were classified according to Gustilo-Anderson as grade I(n-2) and grade II(n-1). The final results were evaluated with the help of Flynn’s criteria. RESULTS: The duration of follow-up ranged between 8 months and 18 months. All fractures united with grade 3 callus at durations ranging between 6 and 12 weeks (average 8.5 weeks). According to Flynn’s criteria, the results were excellent in 30 (83%) patients and satisfactory in 6 (17%) patients. No patient had a poor result. Per-operative complications were nail bending in 2 and cortical perforation in 2 cases. Limb lengthening was seen in 5 cases (1-1.5 cm). Skin irritation at the entry portal site due to prominent nail was noted in 5 cases. CONCLUSION: TENS is a safe and effective treatment option for diaphyseal femoral fractures in children between 6-16years.